Double-Stranded RNA Targeting Dicer-Like Genes Compromises the Pathogenicity of Plasmopara viticola on Grapevine - Haile, Zeraye Mehari; Gebremichael, Daniel Endale; Capriotti, Luca; Molesini, Barbara; Negrini, Francesca; Collina, Marina; Sabbadini, Silvia; Mezzetti, Bruno; Baraldi, Elena (Frontiers in Plant Science, 2021)
Downy mildew caused by Plasmopara viticola is one of the most devastating diseases of grapevine, attacking all green parts of the plant. The damage is severe when the infection at flowering stage is left uncontrolled. P. viticola management consumes a significant amount of classical pesticides applied in vineyards, requiring efficient and environmentally safe disease management options. Spray-induced gene silencing (SIGS), through the application of exogenous double-stranded RNA (dsRNA), has shown promising results for the management of diseases in crops. Here, we developed and tested the potential of dsRNA targeting P. viticola Dicer-like (DCL) genes for SIGS-based crop protection strategy. The exogenous application of PvDCL1/2 dsRNA, a chimera of PvDCL1 and PvDCL2, highly affected the virulence of P. viticola. The reduced expression level of PvDCL1 and PvDCL2 transcripts in infected leaves, treated with PvDCL1/2 dsRNA, was an indication of an active RNA interference mechanism inside the pathogen to compromise its virulence. Besides the protective property, the PvDCL1/2 dsRNA also exhibited a curative role by reducing the disease progress rate of already established infection. Our data provide a promising future for PvDCL1/2 dsRNA as a new generation of RNA-based resistant plants or RNA-based agrochemical for the management of downy mildew disease in grapevine.